2012
DOI: 10.1017/s0067237811000610
|View full text |Cite
|
Sign up to set email alerts
|

Staging the Nation in Fascist Italy's “New Provinces”

Abstract: Read any textbook account of interwar Europe, and “indifference to nation” is not likely to figure as a heading. On the contrary, the talk will be of untrammeled nationalist rivalries leading the continent to ruin. In the territories of Eastern and South Eastern Europe that had once been part of the polyglot Habsburg and Ottoman empires, we will be reminded, nationalist hatred and border conflicts paved the way to World War I. And in the aftermath of that war, the regimes of Mussolini and Hitler took g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Perhaps, more accurately, where Rome's imaginings of italianità were not compatible with those of residents in Trentino-Alto Adige/ Südtirol, a type of hierarchy of Italian-ness emerged that clearly reflected the fluid process of nationbuilding. 120 As the regime's desire to stabilise Italian control in the territory became more urgent, however, its efforts undermined the ability of local officials like Molina to delineate the parameters of italianità (or at least Italian control) in a region rich with its own cultural and political allegiances that by turns competed and overlapped with the interests of the Italian state. At the same time, Italy's struggles to implement more rigid criteria for Italianisation meant the weakening of officials' moral authority, political support and 'totalitarian' façade in the region and, as a result, the inevitable failure of any sort of campaign to establish political or cultural hegemony in Trentino-Alto Adige/Südtirol.…”
Section: Measuring the Distance Between Trent And Romementioning
confidence: 99%
“…Perhaps, more accurately, where Rome's imaginings of italianità were not compatible with those of residents in Trentino-Alto Adige/ Südtirol, a type of hierarchy of Italian-ness emerged that clearly reflected the fluid process of nationbuilding. 120 As the regime's desire to stabilise Italian control in the territory became more urgent, however, its efforts undermined the ability of local officials like Molina to delineate the parameters of italianità (or at least Italian control) in a region rich with its own cultural and political allegiances that by turns competed and overlapped with the interests of the Italian state. At the same time, Italy's struggles to implement more rigid criteria for Italianisation meant the weakening of officials' moral authority, political support and 'totalitarian' façade in the region and, as a result, the inevitable failure of any sort of campaign to establish political or cultural hegemony in Trentino-Alto Adige/Südtirol.…”
Section: Measuring the Distance Between Trent And Romementioning
confidence: 99%
“… Subsequent authors building further on the concept, include: Bolin and Douglas (2017), Brüggemann and Wezel (2019), Feest (2017), Ficeri (2020), Jakoubek (2018, 2021), Kamusella (2016), Leustean (2018), Lichtenstein (2012), Pergher (2012), Polak‐Springer (2020) and Stergar (2012). …”
mentioning
confidence: 99%
“…5 A high degree of legal uniformity is considered advantageous in these accounts as it increased the ability of a state to overcome the 'indifference to nation' of its component regions and link local stability to the preservation of the state. 6 New approaches to state formation, however, have begun to suggest that legal diversity could support the development of a state. Philip Gorski has shown that European states have developed along a variety of paths that are in tension with the primary thrust of theories of state formation.…”
mentioning
confidence: 99%